Antioxidant and antibacterial chitosan / alginate dialdehyde three-layer film and preparation method thereof
Patent Information
- Application Number
- CN202310567562.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-19
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-05-19
AI Technical Summary
[0004]但是,目前,尚无壳聚糖/海藻酸二醛-肉桂醛/壳聚糖-茶多酚三层复合膜的报道
[0025] (1) Sodium alginate (negatively charged) and chitosan (positively charged) carry opposite charges, allowing electrostatic interactions to form. Both sodium alginate and chitosan contain abundant -OH groups, which can form hydrogen bonds. Through electrostatic interactions and hydrogen bonds alone, the interlayer forces of the membrane are weak and prone to delamination, resulting in poor applicability in practical applications. Therefore, this invention modifies the structure of sodium alginate by oxidizing hydroxyl groups to aldehyde groups, allowing Schiff base reactions with the amino groups of chitosan. Chemical bonding can improve the stability of the membrane. Compared with direct blending and layer-by-layer casting, this invention utilizes a combination of layer-by-layer casting and chemical crosslinking to significantly improve the tensile strength/elongation at break, UV/oxygen/water vapor barrier properties, antioxidant properties, and antibacterial properties of the membrane, thereby enhancing the stability and applicability of the membrane.
Smart Images

Figure CN116836422B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biodegradable membrane material preparation, specifically involving an antioxidant and antibacterial chitosan / alginate dialdehyde three-layer membrane and its preparation method. Background Technology
[0002] Traditional petroleum-based packaging materials are produced from non-renewable resources, and their disposal after use causes serious environmental pollution. Currently, natural biopolymers such as polysaccharides, proteins, and lipids are attracting widespread attention due to their potential to replace traditional plastic packaging materials. Among them, chitosan and sodium alginate, natural polysaccharides extracted from crustaceans and brown algae respectively, are being studied for the development of novel food packaging films due to their advantages in biological properties, biodegradability, biocompatibility, and film-forming properties.
[0003] Currently, blended homogeneous membranes and bilayer membranes prepared using chitosan and sodium alginate as matrices have been reported. For example, a blended membrane was prepared using chitosan, sodium alginate, and clove oil as raw materials (Li Yuanchao, A method for preparing food-grade antibacterial plastic, Chinese Invention Patent, 202210658644.4). A sodium alginate-antibacterial agent / chitosan bilayer edible membrane was prepared using CaCl2 crosslinking (Wang Xianghui et al., A sodium alginate-chitosan bilayer edible membrane, its preparation method and its application, Chinese Invention Patent, 201711092409.0).
[0004] However, there are currently no reports on chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer composite membranes. Summary of the Invention
[0005] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.
[0006] In view of the problems existing in the above and / or prior art, the present invention is proposed.
[0007] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing an antioxidant and antibacterial chitosan / alginate dialdehyde three-layer membrane.
[0008] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing an antioxidant and antibacterial chitosan / alginic acid dialdehyde three-layer membrane, comprising,
[0009] Chitosan, acetic acid solution and glycerol are mixed evenly to prepare chitosan film-forming solution, which is then cast into a leveled mold. After drying, thermal crosslinking is induced to form a thermally crosslinked chitosan layer with high barrier properties.
[0010] Sodium alginate was oxidized to alginate dialdehyde and prepared into a solution. Then, it was combined with cinnamaldehyde nanoemulsion to obtain a mixed solution, which was then assembled onto the obtained thermally cross-linked chitosan layer to obtain an intermediate active layer.
[0011] After preparing a chitosan solution composite of tea polyphenols and glycerol, it was assembled onto the obtained intermediate active layer to obtain a thermally cross-linked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenols three-layer membrane.
[0012] As a preferred embodiment of the preparation method of the present invention, the chitosan, acetic acid solution and glycerol are mixed evenly to prepare a chitosan film-forming solution, wherein the ratio of chitosan, glycerol and acetic acid is 10g:3g:1000ml and the concentration of acetic acid solution is 1%.
[0013] As a preferred embodiment of the preparation method described in this invention, the thermally induced crosslinking forms a thermally crosslinked chitosan layer with high barrier properties, wherein the thermal induction temperature is 100-110°C and the treatment time is 12-24 h.
[0014] As a preferred embodiment of the preparation method described in this invention, the sodium alginate is oxidized to alginate dialdehyde and prepared into a solution, and then compounded with cinnamaldehyde nanoemulsion to obtain a mixed solution, wherein the concentration of alginate dialdehyde in the mixed solution is 1-8 mg / mL and the concentration of cinnamaldehyde nanoemulsion is 1%-15%.
[0015] In a preferred embodiment of the preparation method described in this invention, the mixed solution further includes glycerol, with a glycerol concentration of 0.1% to 0.5%.
[0016] In a preferred embodiment of the preparation method described in this invention, the film-forming conditions of the intermediate active layer are 25°C to 50°C.
[0017] As a preferred embodiment of the preparation method described in this invention, the preparation method of the alginate dialdehyde includes:
[0018] Sodium alginate was dissolved in a mixture of anhydrous ethanol and distilled water. Sodium periodate was added and the mixture was reacted in the dark at 40°C for 6 hours. Ethylene glycol was then added and the mixture was stirred for 30 minutes to terminate the reaction.
[0019] Dialyze the reaction solution for 24 hours, changing the distilled water several times during this period, until no iodate remains;
[0020] Finally, the dialysis solution was freeze-dried to obtain alginate dialdehyde.
[0021] In a preferred embodiment of the preparation method described in this invention, after preparing the chitosan solution combined with tea polyphenols and glycerol, it is assembled onto the obtained intermediate active layer, wherein the chitosan concentration is 0.5% to 3.0%, the glycerol concentration is 0.1% to 0.5%, the tea polyphenol concentration is 0.01% to 0.50%, and the film-forming conditions are 25℃ to 50℃.
[0022] Another objective of this invention is to overcome the shortcomings of the prior art and provide a method for preparing an antioxidant and antibacterial chitosan / alginic acid dialdehyde three-layer membrane. The prepared chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer membrane has a tensile strength of 15 MPa to 25 MPa, an elongation at break of 18% to 22%, and a water vapor barrier property of 2 × 10⁻⁶. -12 ~4×10 -12 g·m -1 ·s -1 ·Pa -1 The oxygen barrier property is 3×10 -7 -6×10 -7 g·m -1 ·s -1 It has a DPPH free radical scavenging rate of 18-98% and has antibacterial effects against Staphylococcus aureus and Escherichia coli.
[0023] Another objective of this invention is to overcome the shortcomings of the prior art and provide an application of a chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer film in the preparation of food-grade packaging materials.
[0024] Beneficial effects of this invention:
[0025] (1) Sodium alginate (negatively charged) and chitosan (positively charged) carry opposite charges, allowing electrostatic interactions to form. Both sodium alginate and chitosan contain abundant -OH groups, which can form hydrogen bonds. Through electrostatic interactions and hydrogen bonds alone, the interlayer forces of the membrane are weak and prone to delamination, resulting in poor applicability in practical applications. Therefore, this invention modifies the structure of sodium alginate by oxidizing hydroxyl groups to aldehyde groups, allowing Schiff base reactions with the amino groups of chitosan. Chemical bonding can improve the stability of the membrane. Compared with direct blending and layer-by-layer casting, this invention utilizes a combination of layer-by-layer casting and chemical crosslinking to significantly improve the tensile strength / elongation at break, UV / oxygen / water vapor barrier properties, antioxidant properties, and antibacterial properties of the membrane, thereby enhancing the stability and applicability of the membrane.
[0026] (2) Compared with the blended membrane of chitosan and sodium alginate, the three-layer membrane prepared by the present invention can make active substances (such as cinnamaldehyde) slowly released by utilizing the physical barrier effect of the matrix, avoiding the explosive release of active substances caused by direct blending; compared with the bilayer membrane of chitosan and sodium alginate prepared by encapsulation system such as loaded nanoparticles and microcapsules, the present invention avoids the defects of complex encapsulation method and low encapsulation rate, and can achieve a similar sustained release effect by simply casting and stacking layers. Attached Figure Description
[0027] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein:
[0028] Figure 1 The infrared spectra of sodium alginate and alginate dialdehyde provided in Example 1 of this invention are shown.
[0029] Figure 2 The infrared spectra of the thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan trilayer membranes of Comparative Example 1 and Examples 2-6 in this invention are shown.
[0030] Figure 3 These are scanning electron microscope (SEM) images of the thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan trilayer membranes of Comparative Example 1 and Examples 2-6 in this invention.
[0031] Figure 4 The release curves of cinnamaldehyde in 10% ethanol and 95% ethanol food simulants are shown in this invention.
[0032] Figure 5 This study examines the oxidizing properties of the thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan trilayer membranes in Comparative Example 1 and Examples 2-6 of this invention.
[0033] Figure 6 This study examines the antibacterial properties of the thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan trilayer membranes in Comparative Example 1 and Examples 2-6 of this invention.
[0034] Figure 7 The oxidation properties of the thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol triple membranes in Examples 5 and 7-10 of this invention.
[0035] Figure 8 The antibacterial properties of the thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol triple membranes in Examples 5 and 7-10 of this invention.
[0036] Figure 9 This describes the effects of different treatments provided in Example 11 of this invention on the TBARS and SH of fish fillets.
[0037] Figure 10 This illustrates the effects of different treatments provided in Example 11 of this invention on the microorganisms in fish fillets. Detailed Implementation
[0038] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0039] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0040] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0041] Example 1
[0042] Dissolve 10 g of sodium alginate in 100 ml of anhydrous ethanol and 400 ml of distilled water, add 15 g of sodium periodate, and react in the dark at 40 °C for 6 hours. Then add 20 ml of ethylene glycol and stir for 30 minutes to terminate the reaction.
[0043] Dialyze the reaction solution for 24 hours, changing the distilled water several times during this period, until no iodate remains.
[0044] Finally, the dialysate was freeze-dried to recover ADA.
[0045] Example 2
[0046] A thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan three-layer membrane, the method of which is as follows:
[0047] (1) Dissolve 10 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 3 g (m / v) of glycerol in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold, drain and shape it at 25°C, and then place it in a constant temperature and humidity chamber for 48 hours after treatment at 110°C for 24 hours to obtain a thermally cross-linked chitosan layer.
[0048] (2) Dissolve 20 g of alginate dialdehyde powder (oxidation degree 77%; m / v) and 6 g (m / v) of glycerol in 0.5 L of distilled water and stir for 1 hour to fully dissolve the alginate dialdehyde.
[0049] Meanwhile, cinnamaldehyde and Tween 80 were added to distilled water at a ratio of 1:2, and a 2% (v / v) cinnamaldehyde nanoemulsion was prepared by homogenization and ultrasound.
[0050] Cinnamaldehyde nanoemulsion and alginate dialdehyde solution were mixed at a volume ratio of 1:3, poured evenly onto a thermally cross-linked chitosan layer, and gelled at 25°C to obtain an alginate dialdehyde-cinnamaldehyde layer.
[0051] (3) Dissolve 5 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 1.5 g (m / v) of glycerol in 1 L (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold and drain at 25 °C to form a thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan three-layer film.
[0052] Example 3
[0053] A thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan three-layer membrane, the method of which is as follows:
[0054] (1) Dissolve 10 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 3 g (m / v) of glycerol in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold, drain and shape it at 25°C, treat it at 110°C for 24 hours, and then place it in a constant temperature and humidity chamber for 48 hours to equilibrate and obtain a thermally cross-linked chitosan layer.
[0055] (2) Dissolve 20 g of alginate dialdehyde powder (oxidation degree 77%; m / v) and 6 g (m / v) of glycerol in 0.5 L of distilled water and stir for 1 hour to fully dissolve the alginate dialdehyde.
[0056] Meanwhile, cinnamaldehyde and Tween 80 were added to distilled water at a ratio of 1:2, and a 4% (v / v) cinnamaldehyde nanoemulsion was prepared by homogenization and ultrasound.
[0057] Cinnamaldehyde nanoemulsion and alginate dialdehyde solution were mixed at a volume ratio of 1:3, poured evenly onto a thermally cross-linked chitosan layer, and gelled at 25°C to obtain an alginate dialdehyde-cinnamaldehyde layer.
[0058] (3) Dissolve 5 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 1.5 g (m / v) of glycerol in 1 L (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold and drain at 25 °C to form a thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan three-layer film.
[0059] Example 4
[0060] A thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan three-layer membrane, the method of which is as follows:
[0061] (1) Dissolve 10 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 3 g (m / v) of glycerol in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold, drain and shape it at 25°C, treat it at 110°C for 24 hours, and then place it in a constant temperature and humidity chamber for 48 hours to equilibrate and obtain a thermally cross-linked chitosan layer.
[0062] (2) Dissolve 20 g of alginate dialdehyde powder (oxidation degree 77%; m / v) and 6 g (m / v) of glycerol in 0.5 L of distilled water and stir for 1 hour to fully dissolve the alginate dialdehyde. At the same time, add cinnamaldehyde and Tween 80 to distilled water at a ratio of 1:2 and prepare a 6% (v / v) cinnamaldehyde nanoemulsion by homogenization and sonication. Mix the cinnamaldehyde nanoemulsion with the alginate dialdehyde solution at a volume ratio of 1:3, pour the mixture evenly onto the thermally crosslinked chitosan layer, and gel at 25 °C to obtain the alginate dialdehyde-cinnamaldehyde layer;
[0063] (3) Dissolve 5 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 1.5 g (m / v) of glycerol in 1 L (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold and drain at 25 °C to form a thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan three-layer film.
[0064] Example 5
[0065] A thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan three-layer membrane, the method of which is as follows:
[0066] (1) Dissolve 10 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 3 g (m / v) of glycerol in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold, drain and shape it at 25°C, treat it at 110°C for 24 hours, and then place it in a constant temperature and humidity chamber for 48 hours to equilibrate and obtain a thermally cross-linked chitosan layer.
[0067] (2) Dissolve 20 g of alginate dialdehyde powder (oxidation degree 77%; m / v) and 6 g (m / v) of glycerol in 0.5 L of distilled water and stir for 1 hour to fully dissolve the alginate dialdehyde. At the same time, add cinnamaldehyde and Tween 80 to distilled water at a ratio of 1:2 and prepare an 8% (v / v) cinnamaldehyde nanoemulsion by homogenization and sonication. Mix the cinnamaldehyde nanoemulsion with the alginate dialdehyde solution at a volume ratio of 1:3, pour the mixture evenly onto the thermally crosslinked chitosan layer, and gel at 25 °C to obtain the alginate dialdehyde-cinnamaldehyde layer;
[0068] (3) Dissolve 5 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 1.5 g (m / v) of glycerol in 1 L (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold and drain at 25 °C to form a thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan three-layer film.
[0069] Example 6
[0070] A thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan three-layer membrane, the method of which is as follows:
[0071] (1) Dissolve 10 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 3 g (m / v) of glycerol in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold, drain and shape it at 25°C, treat it at 110°C for 24 hours, and then place it in a constant temperature and humidity chamber for 48 hours to equilibrate and obtain a thermally cross-linked chitosan layer.
[0072] (2) Dissolve 20 g of alginate dialdehyde powder (oxidation degree 77%; m / v) and 6 g (m / v) of glycerol in 0.5 L of distilled water and stir for 1 hour to fully dissolve the alginate dialdehyde. At the same time, add cinnamaldehyde and Tween 80 to distilled water at a ratio of 1:2 and prepare a 10% (v / v) cinnamaldehyde nanoemulsion by homogenization and sonication. Mix the cinnamaldehyde nanoemulsion with the alginate dialdehyde solution at a volume ratio of 1:3, pour the mixture evenly onto the thermally cross-linked chitosan layer, and gel at 25 °C to obtain the alginate dialdehyde-cinnamaldehyde layer;
[0073] (3) Dissolve 5 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 1.5 g (m / v) of glycerol in 1 L (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold and drain at 25 °C to form a thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan three-layer film.
[0074] Example 7
[0075] A thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer membrane, the method of which is as follows:
[0076] (1) Dissolve 10 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 3 g (m / v) of glycerol in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold, drain and shape it at 25°C, treat it at 110°C for 24 hours, and then place it in a constant temperature and humidity chamber for 48 hours to equilibrate and obtain a thermally cross-linked chitosan layer.
[0077] (2) Dissolve 20 g of alginate dialdehyde powder (oxidation degree 77%; m / v) and 6 g (m / v) of glycerol in 0.5 L of distilled water and stir for 1 hour to fully dissolve the alginate dialdehyde. At the same time, add cinnamaldehyde and Tween 80 to distilled water at a ratio of 1:2 and prepare an 8% (v / v) cinnamaldehyde nanoemulsion by homogenization and sonication. Mix the cinnamaldehyde nanoemulsion with the alginate dialdehyde solution at a volume ratio of 1:3, pour the mixture evenly onto the thermally crosslinked chitosan layer, and gel at 25 °C to obtain the alginate dialdehyde-cinnamaldehyde layer;
[0078] (3) Dissolve 5 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v), 1.5 g (m / v) of glycerol and 0.02% of tea polyphenols in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve, remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan-tea polyphenol film-forming solution, pour it into a leveled mold, and drain at 25°C to form a thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer film.
[0079] Example 8
[0080] A thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer membrane, the method of which is as follows:
[0081] (1) Dissolve 10 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 3 g (m / v) of glycerol in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold, drain and shape it at 25°C, treat it at 110°C for 24 hours, and then place it in a constant temperature and humidity chamber for 48 hours to equilibrate and obtain a thermally cross-linked chitosan layer.
[0082] (2) Dissolve 20 g of alginate dialdehyde powder (oxidation degree 77%; m / v) and 6 g (m / v) of glycerol in 0.5 L of distilled water and stir for 1 hour to fully dissolve the alginate dialdehyde. At the same time, add cinnamaldehyde and Tween 80 to distilled water at a ratio of 1:2 and prepare an 8% (v / v) cinnamaldehyde nanoemulsion by homogenization and sonication. Mix the cinnamaldehyde nanoemulsion with the alginate dialdehyde solution at a volume ratio of 1:3, pour the mixture evenly onto the thermally crosslinked chitosan layer, and gel at 25 °C to obtain the alginate dialdehyde-cinnamaldehyde layer;
[0083] (3) Dissolve 5 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v), 1.5 g (m / v) of glycerol and 0.04% of tea polyphenols in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve, remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan-tea polyphenol film-forming solution, pour into a leveled mold, and drain at 25°C to form a thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer film.
[0084] Example 9
[0085] A thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer membrane, the method of which is as follows:
[0086] (1) Dissolve 10 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 3 g (m / v) of glycerol in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold, drain and shape it at 25°C, treat it at 110°C for 24 hours, and then place it in a constant temperature and humidity chamber for 48 hours to equilibrate and obtain a thermally cross-linked chitosan layer.
[0087] (2) Dissolve 20 g of alginate dialdehyde powder (oxidation degree 77%; m / v) and 6 g (m / v) of glycerol in 0.5 L of distilled water and stir for 1 hour to fully dissolve the alginate dialdehyde. At the same time, add cinnamaldehyde and Tween 80 to distilled water at a ratio of 1:2 and prepare an 8% (v / v) cinnamaldehyde nanoemulsion by homogenization and sonication. Mix the cinnamaldehyde nanoemulsion with the alginate dialdehyde solution at a volume ratio of 1:3, pour the mixture evenly onto the thermally crosslinked chitosan layer, and gel at 25 °C to obtain the alginate dialdehyde-cinnamaldehyde layer;
[0088] (3) Dissolve 5 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v), 1.5 g (m / v) of glycerol and 0.06% of tea polyphenols in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve, remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan-tea polyphenol film-forming solution, pour into a leveled mold, and drain at 25°C to form a thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer film.
[0089] Example 10
[0090] A thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer membrane, the method of which is as follows:
[0091] (1) Dissolve 10 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 3 g (m / v) of glycerol in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold, drain and shape it at 25°C, treat it at 110°C for 24 hours, and then place it in a constant temperature and humidity chamber for 48 hours to equilibrate and obtain a thermally cross-linked chitosan layer.
[0092] (2) Dissolve 20 g of alginate dialdehyde powder (oxidation degree 77%; m / v) and 6 g (m / v) of glycerol in 0.5 L of distilled water and stir for 1 hour to fully dissolve the alginate dialdehyde. At the same time, add cinnamaldehyde and Tween 80 to distilled water at a ratio of 1:2 and prepare an 8% (v / v) cinnamaldehyde nanoemulsion by homogenization and sonication. Mix the cinnamaldehyde nanoemulsion with the alginate dialdehyde solution at a volume ratio of 1:3, pour the mixture evenly onto the thermally crosslinked chitosan layer, and gel at 25 °C to obtain the alginate dialdehyde-cinnamaldehyde layer;
[0093] (3) Dissolve 5 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v), 1.5 g (m / v) of glycerol and 0.08% of tea polyphenols in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve, remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan-tea polyphenol film-forming solution, pour into a leveled mold, and drain at 25°C to form a thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer film.
[0094] Example 11
[0095] An application of a thermally cross-linked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer membrane, the method of which is as follows:
[0096] (1) Dissolve 10 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 3 g (m / v) of glycerol in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold, drain and shape it at 25°C, treat it at 110°C for 24 hours, and then place it in a constant temperature and humidity chamber for 48 hours to equilibrate and obtain a thermally cross-linked chitosan layer.
[0097] (2) Dissolve 20 g of alginate dialdehyde powder (oxidation degree 77%; m / v) and 6 g (m / v) of glycerol in 0.5 L of distilled water and stir for 1 hour to fully dissolve the alginate dialdehyde. At the same time, add cinnamaldehyde and Tween 80 to distilled water at a ratio of 1:2 and prepare an 8% (v / v) cinnamaldehyde nanoemulsion by homogenization and sonication. Mix the cinnamaldehyde nanoemulsion with the alginate dialdehyde solution at a volume ratio of 1:3, pour the mixture evenly onto the thermally crosslinked chitosan layer, and gel at 25 °C to obtain the alginate dialdehyde-cinnamaldehyde layer;
[0098] (3) Dissolve 5 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v), 1.5 g (m / v) of glycerol and 0.06% of tea polyphenols in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve, remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan-tea polyphenol film-forming solution, pour into a leveled mold, and drain at 25°C to form a thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer membrane, named AF membrane.
[0099] (4) Collect fresh grass carp meat and cut it into pieces approximately 4×3×1.5cm in size. 3 The fish pieces were cut into chunks, then rinsed with pre-cooled sterile water at 4°C and the surface moisture was patted dry. The fish chunks were then treated as follows: no wrapping (CK group), wrapped in plastic wrap (PE group), wrapped in CS film (CS group), and wrapped in active film (AF group). They were then placed in a 4°C refrigerator, and samples were taken every 2 days until day 8.
[0100] (5) Weigh 2.0 g of chopped fish meat, add 10 mL of 10% (m / v) trichloroacetic acid (TCA) solution pre-cooled at 4℃, mix, homogenize at 10000 r / min for 1 min, and then centrifuge at 8000 g and 4℃ for 10 min. Take 5 mL of the supernatant into a centrifuge tube, add 5 mL of 0.02 mol / L thiobarbituric acid (TBA) solution, react at 95℃ for 20 min, and after cooling, measure the absorbance at 532 nm. Calculate the thiobarbituric acid value (TBARS) using the 1,1,3,3-tetraethoxypropane standard curve and express it as mg malondialdehyde / kg sample.
[0101] (6) Weigh 5.0g of chopped fish meat into a sterile homogenizing bag, add 45mL of sterile physiological saline, seal, and tap for 2 minutes. Measure the mixture and dilute it 10 times consecutively. Select three appropriate dilutions and spread them onto plate counting agar, Pseudomonas CFC selective medium, and iron agar, respectively. Then place them in a 30℃ incubator. After 3 days, count the total number of colonies, Pseudomonas, and H2S-producing bacteria, and express the results as log. 10 CFU / g.
[0102] The thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan trilayer membranes and their applications provided in comparative examples and Examples 1-11 of the present invention were tested, and the results are as follows:
[0103] The oxidation of sodium alginate causes the hydroxyl groups on the C-2 and C-3 bonds of its repeating units to be cleaved into aldehyde groups. For example... Figure 1 As shown, compared with the infrared spectrum of sodium alginate, the infrared spectrum of dialgin at 1730 cm⁻¹... -1 -1740cm -1A weak peak appeared, which is the characteristic peak of the aldehyde group, confirming that the aldehyde group was introduced through oxidation.
[0104] like Figure 2 As shown, the membrane at 3500 cm⁻¹ -1 -3000cm -1 The range contains broad peaks corresponding to the tensile vibrations of OH and NH. (1628 cm⁻¹) -1 The position corresponds to the tensile vibration of CN, indicating that a Schiff base has formed between the aldehyde and the amino group. 1549cm -1 and 1407cm -1 The peaks at these locations blue-shifted to 1558 cm⁻¹ and 1450 cm⁻¹, respectively, indicating increased consumption of amino groups and formation of Schiff bases. FTIR confirmed the existence of Schiff bases, hydrogen bonds, and electrostatic interactions between ADA and CS.
[0105] like Figure 3 As shown, the three-layer structure of all membranes is relatively clear, and the layers are tightly bonded. The alginate dialdehyde layer of the comparative membrane is uniform, smooth, continuous, and free of pores. However, the results of the membranes in Examples 2-6 show that they become rough and porous after the addition of cinnamaldehyde nanoemulsion, mainly due to the aggregation of cinnamaldehyde nanoemulsion droplets and evaporation after flocculation during the film drying process. In addition, the addition of different concentrations of cinnamaldehyde nanoemulsion also shows that the pores become smaller and the matrix becomes more uniform.
[0106] As shown in Table 1, all membranes have similar thicknesses, ranging from 0.150 mm to 0.172 mm. The tensile strength and elongation at break of the comparative membrane are 15.02 MPa and 17.53%, respectively.
[0107] The results for the films in Examples 2-6 indicate that the addition of cinnamaldehyde nanoemulsion improved the tensile strength of the multilayer films. This is likely because the smaller size of the cinnamaldehyde nanoemulsion promotes the formation of a continuous network structure in the polymer, leading to a slight increase in tensile strength. The change in elongation at break was consistent with the tensile strength; the addition of cinnamaldehyde nanoemulsion significantly increased the elongation at break (p<0.05), which can be attributed to the plasticizing effect of the cinnamaldehyde nanoemulsion, improving the flexibility of the film and making it more ductile.
[0108] Table 1. Thickness, mechanical properties, and barrier properties of the thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan trilayer films in Comparative Examples 1 and Examples 2-6
[0109]
[0110] Note: Values are mean ± standard deviation, and letters indicate statistical significance (p < 0.05).
[0111] Furthermore, the water vapor permeability of the comparative membrane was 3.56 × 10⁻⁶. -12g·m -1 ·s -1 ·Pa -1 The results of Examples 2-6 showed that the water vapor permeability of the film samples initially decreased significantly (p<0.05) after the addition of cinnamaldehyde nanoemulsion, due to the hydrophobic structure of the film. With increasing concentration, the water vapor permeability then increased, because the evaporation of cinnamaldehyde during drying allows pores to form in the film structure, increasing the number of available channels for water vapor movement. The oxygen permeability of the comparative film was 5.80 × 10⁻⁶. -7 g·m -1 ·s -1 .
[0112] The results from Examples 2-6 show that after adding cinnamaldehyde nanoemulsion, the trend of oxygen permeability is consistent with that of water vapor permeability, i.e., it first decreases and then increases. The decrease in oxygen permeability may be related to the combination of oxygen with amino groups in the membrane, while the increase in oxygen permeability may be related to the porosity in the membrane structure, thereby increasing the space and pathway for oxygen to move within the membrane. This is consistent with the results from scanning electron microscopy.
[0113] Release curves of cinnamaldehyde in two different food simulants are as follows: Figure 4 As shown in the figure. The results indicate that the release rate of cinnamaldehyde in the 10% ethanol solution is lower than that in the 95% ethanol solution. The release behavior of cinnamaldehyde from the membrane occurs in two steps. In the first step, liquid molecules penetrate the polymer matrix, causing expansion and weakening of the polymer network structure. Then, cinnamaldehyde molecules diffuse from the interior of the membrane into the simulated solution until thermodynamic equilibrium is reached. The properties of the food simulated agent (such as pH value, water activity, etc.) are key factors affecting the migration of essential oils and thus the antibacterial properties of the membrane. The cinnamaldehyde release is highest in the 95% ethanol solution, reaching equilibrium in just 40 minutes. This is because cinnamaldehyde has high solubility in solvents with low polarity, such as ethanol. The release of cinnamaldehyde from the 10% ethanol solution takes 6 hours, possibly because smaller molecules, such as nanoemulsions, diffuse more rapidly within the polymer matrix.
[0114] like Figure 5 As shown, the comparative membrane exhibited a DPPH· scavenging activity of approximately 21%, which is attributed to the relatively weak antioxidant capacity of chitosan itself. For the membranes of Examples 2-6, the DPPH· scavenging activity gradually increased with increasing concentration of cinnamaldehyde nanoemulsion, reaching approximately 80% when 10% cinnamaldehyde nanoemulsion was added. This is because the increased cinnamaldehyde content in the film enhances its ability to scavenge DPPH· free radicals, as its ability to scavenge DPPH· free radicals depends on the hydroxyl group and single electron donor on the benzene ring of cinnamaldehyde, thereby playing a role in stabilizing free radicals.
[0115] like Figure 6As shown, compared with the comparative membrane, the number of viable Escherichia coli and Staphylococcus aureus was significantly reduced after 24 hours of treatment with membranes containing more than 6% cinnamaldehyde nanoemulsion (p<0.05). This indicates that the hydrophobic molecules of cinnamaldehyde disrupt cell membrane permeability, inhibit normal cell function, and ultimately lead to the leakage of proteins, nucleic acids, and potassium ions from the cell interior. The membranes of Comparative Example 1, Example 2, and Example 3 showed poor inhibitory effects on Escherichia coli due to their lower cinnamaldehyde concentrations. Furthermore, the chitosan in these multilayer membranes did not exhibit significant antibacterial activity, possibly because the formation of the polyelectrolyte complex reduced the positive charge density on the chitosan surface, limiting the electrostatic interaction between chitosan and the microbial cell membrane. In addition, the growth curves of Escherichia coli and Staphylococcus aureus were closely correlated with the release of cinnamaldehyde. In samples treated with membranes containing more than 6% cinnamaldehyde nanoemulsion, the number of Escherichia coli decreased in the first 6 hours and then gradually increased. Most of the CA in the membrane was also released within the first 6 hours.
[0116] As shown in Table 2, the thickness of all films ranged from 0.148 mm to 0.189 mm. The TS and EB values of the film in Example 5 were 24.61 MPa and 22.21%, respectively. With increasing tea polyphenol volume, the tensile strength first increased and then decreased. The addition of tea polyphenols initially weakened the internal hydrogen bonds between chitosan molecules and supported the formation of new hydrogen bonds, improving the mechanical properties of the film. However, with increasing tea polyphenol volume, excess tea polyphenol molecules restricted the bonding of chitosan molecules, reducing the secondary forces between polymer macromolecules. The change in elongation at break showed no obvious trend.
[0117] Table 2 also shows the water vapor permeability and oxygen permeability of membranes with different amounts of tea polyphenols. For the membrane in Example 5, the water vapor permeability was 1.59 × 10⁻⁶. -12 g·m -1 ·s -1 ·Pa -1 As the volume of tea polyphenols increases, both water vapor permeability and oxygen permeability increase. This is likely because the interaction between tea polyphenols and chitosan molecules results in a more uniform network structure, reducing the free membrane of the polymer matrix and restricting the mobility of the polymer chains. Therefore, the passage of oxygen molecules is limited. Furthermore, with the increase in the volume of tea polyphenols, excess tea polyphenol molecules may also restrict the passage of oxygen molecules through the membrane.
[0118] Table 2. Thickness, mechanical properties, and barrier properties of the thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol trilayer films of Examples 5 and 7-10.
[0119]
[0120] Note: Values are mean ± standard deviation, and letters indicate statistical significance (p < 0.05).
[0121] like Figure 7 As shown. The membrane of Example 5 exhibited the lowest antioxidant capacity, mainly due to the amino group at the C-2 position of chitosan and the phenolic hydroxyl group and single electron donor of tea polyphenols. However, the addition of tea polyphenols significantly improved the antioxidant activity of the membrane (p>0.05), which was higher than that of the membrane of Example 5 and showed a high concentration dependence, especially the 0.06% and 0.08% tea polyphenol groups, which showed strong antioxidant capacity. This phenomenon may be related to the increased hydrogen atom and electron transfer capacity due to the increased concentration of tea polyphenols.
[0122] Figure 8 The antibacterial properties of membranes with different amounts of tea polyphenols against Staphylococcus aureus and Escherichia coli were demonstrated. Example 5 showed that the membrane itself possessed antibacterial activity, reducing the proliferation of Staphylococcus aureus and Escherichia coli, indicating that chitosan and cinnamaldehyde have antibacterial activity. The antibacterial activity of chitosan mainly derives from the interaction between the positively charged amino groups in chitosan and the negatively charged molecules on the cell surface, affecting cell membrane permeability and thus achieving an antibacterial effect. Cinnamaldehyde itself has antibacterial properties, slowing the growth of Staphylococcus aureus and Escherichia coli. Adding different amounts of tea polyphenols to the membrane further inhibited microbial reproduction to a greater extent because tea polyphenols can damage bacterial cell membranes and inhibit their lipid synthesis or enzyme activity.
[0123] Lipid oxidation leads to rancidity and discoloration of fish, thereby accelerating the degradation of amino acids and proteins. At day 0, the TBARS of the fish was 0.182 mg malondialdehyde / kg sample (see...). Figure 9 Compared with the CK group, the TBARS of the PE, CS, and AF groups showed a decreasing trend, and the TBARS of the AF group fish fillets was significantly lower than that of the CK, PE, and CS groups when stored for 6-8 days. On day 8, the AF group fish fillets had the lowest TBARS, with a value of 0.518 mg malondialdehyde / kg sample. The results indicate that the AF membrane has a significant delaying effect on lipid oxidation, which is related to the antioxidant activity of CS, CA, and TP in the AF membrane.
[0124] SH content is related to the degree of protein oxidation in fish fillets. At 0 days, the SH content of fish meat is 7.58 mol / 10⁵ g protein. With prolonged storage, the SH content in fish fillets shows a decreasing trend. Figure 9 This phenomenon may be related to the protein degradation of fish meat under the action of enzymes and microorganisms, leading to the exposure of sulfhydryl groups, which are then oxidized into disulfide bonds. Compared with the CK group, the CS and AF groups showed significant reductions after 8 days of storage. In particular, the SH level in the AF group was the highest, indicating the lowest degree of protein oxidation and the least amount of reactive oxygen species attack on the protein.
[0125] like Figure 10 As shown, the total bacterial count, Pseudomonas, and hydrogen sulfide-producing bacteria in the fish fillets on day 0 were 3.52 log10 CFU / g, 2.72 log10 CFU / g, and 2.75 log10 CFU / g, respectively. The total bacterial count, Pseudomonas, and hydrogen sulfide-producing bacteria in all groups increased with increasing storage days. There were no significant differences in the total bacterial count, Pseudomonas, and hydrogen sulfide-producing bacteria between the CK and PE groups. The bacterial count in the fish fillets of the CS group was significantly lower than that of the control group, which is attributed to the antibacterial effect of CS itself. The addition of CA and TP to the CS membrane inhibited bacterial growth, consistent with the trend of the antibacterial properties of the membrane described above. Furthermore, the greatest difference in microbial counts was observed between the AF and CS groups at day 6. This may be related to the antibacterial effects of CS, CA, and TP.
[0126] Comparative Example 1
[0127] A thermally crosslinked chitosan / alginic dialdehyde / chitosan three-layer membrane, the method of which is as follows:
[0128] (1) Dissolve 10 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 3 g (m / v) of glycerol in 1 L of 1% (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold, drain and shape it at 25°C, treat it at 110°C for 24 hours, and then place it in a constant temperature and humidity chamber for 48 hours to equilibrate and obtain a thermally cross-linked chitosan layer.
[0129] (2) Dissolve 20 g of alginate dialdehyde powder (oxidation degree 77%; m / v) and 6 g (m / v) of glycerol in 0.5 L of distilled water and stir for 1 hour to fully dissolve the alginate dialdehyde. Mix the distilled water and the alginate dialdehyde solution at a volume ratio of 1:3, pour the mixture evenly onto the thermally cross-linked chitosan layer, and allow it to gel at 25 °C to obtain the alginate dialdehyde-cinnamaldehyde layer;
[0130] (3) Dissolve 5 g of chitosan powder (molecular weight 200 kDa, degree of deacetylation 85%; m / v) and 1.5 g (m / v) of glycerol in 1 L (v / v) acetic acid solution, stir for 4 hours to fully dissolve the chitosan, and remove insoluble impurities and bubbles by centrifugation to form a homogeneous chitosan solution. Pour the solution into a leveled mold and drain at 25 °C to form a thermally crosslinked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan three-layer film.
[0131] In summary, the chitosan / alginic acid dialdehyde three-layer membrane prepared by this invention has good mechanical properties, barrier ability, antioxidant and antibacterial activity. It is more suitable for perishable foods such as fruits, vegetables, aquatic products and meat products, and has the potential to avoid oxidation and microbial contamination during transportation, storage and processing.
[0132] Sodium alginate (negatively charged) and chitosan (positively charged) carry opposite charges, allowing for electrostatic interactions. Both sodium alginate and chitosan contain abundant -OH groups, enabling hydrogen bonding. However, relying solely on electrostatic interactions and hydrogen bonding results in weak interlayer forces in the membrane, leading to easy delamination and poor applicability in practical applications. Therefore, this invention modifies the structure of sodium alginate by oxidizing hydroxyl groups to aldehyde groups, allowing for Schiff base reactions with the amino groups of chitosan. This chemical bonding enhances membrane stability. Compared to direct blending and layer-by-layer casting, this invention utilizes a combination of layer-by-layer casting and chemical crosslinking to significantly improve the mechanical, barrier, and hydrophobic properties of the film.
[0133] Currently, both homogeneous blended membranes and bilayer membranes based on chitosan and sodium alginate have been reported. Compared to blended membranes of chitosan and sodium alginate, the three-layer membrane prepared in this invention utilizes the physical barrier effect of the matrix to allow for the slow release of active substances (such as cinnamaldehyde), avoiding the explosive release of active substances caused by direct blending. Compared to bilayer membranes of chitosan and sodium alginate prepared by encapsulation systems such as loaded nanoparticles and microcapsules, this invention avoids the defects of complex encapsulation methods and low encapsulation rates, achieving a similar sustained-release effect simply by layer-by-layer casting and stacking.
[0134] This invention utilizes chitosan and dialgaldehyde as film-forming matrices, and cinnamaldehyde and tea polyphenols as active ingredients. Based on chemical modification and layer-by-layer casting technology, a thermally cross-linked chitosan / dialgaldehyde-cinnamaldehyde / chitosan-tea polyphenol three-layer composite membrane with excellent physicochemical, antibacterial, and antioxidant properties is constructed. Chitosan and dialgaldehyde increase the interlayer tightness through Schiff base covalent bonds, electrostatic forces, and hydrogen bonds. The combined use of cinnamaldehyde and tea polyphenols improves the function of individual active substances, enhancing their antioxidant and antibacterial properties. Compared to blended membranes of chitosan and sodium alginate, the three-layer membrane prepared by this invention utilizes the physical barrier effect of the matrix to allow for the slow release of active substances, avoiding the explosive release of active substances caused by direct blending. Compared to bilayer membranes of chitosan and sodium alginate prepared using encapsulation systems such as loaded nanoparticles and microcapsules, this invention avoids the defects of complex encapsulation methods and low encapsulation rates, achieving a similar sustained-release effect simply through layer-by-layer casting. Therefore, the technology of this invention can provide new ideas for finding alternatives to plastic packaging and provide technical support for solving the technical bottleneck of fresh and perishable food preservation.
[0135] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.
Claims
1. A method for preparing an antioxidant and antibacterial chitosan / alginic acid dialdehyde three-layer membrane, characterized in that: include, Chitosan, acetic acid solution and glycerol are mixed evenly to prepare chitosan film-forming solution, which is then cast into a leveled mold. After drying, thermal crosslinking is induced to form a thermally crosslinked chitosan layer with high barrier properties. Sodium alginate was oxidized to alginate dialdehyde and prepared into a solution. Then, it was combined with cinnamaldehyde nanoemulsion to obtain a mixed solution, which was then assembled onto the obtained thermally cross-linked chitosan layer to obtain an intermediate active layer. After preparing a chitosan solution composite of tea polyphenols and glycerol, it was assembled onto the obtained intermediate active layer to obtain a thermally cross-linked chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenols three-layer membrane.
2. The preparation method according to claim 1, characterized in that: The chitosan film-forming solution is prepared by uniformly mixing chitosan, acetic acid solution and glycerol, wherein the ratio of chitosan, glycerol and acetic acid is 10g:3g:1000ml and the concentration of acetic acid solution is 1% (v / v).
3. The preparation method according to claim 1, characterized in that: The thermally induced crosslinking forms a thermally crosslinked chitosan layer with high barrier properties, wherein the thermal induction temperature is 100~110℃ and the treatment time is 12~24h.
4. The preparation method according to claim 1, characterized in that: The process involves oxidizing sodium alginate to alginate dialdehyde and preparing a solution, then compounding it with cinnamaldehyde nanoemulsion to obtain a mixed solution. The concentration of alginate dialdehyde in the mixed solution is 1~8 mg / mL, and the concentration of cinnamaldehyde nanoemulsion is 1%~15% (v / v).
5. The preparation method according to claim 4, characterized in that: The mixed solution also includes glycerol, with a glycerol concentration of 0.1% to 0.5%.
6. The preparation method according to any one of claims 1, 4 or 5, characterized in that: The film-forming conditions for the intermediate active layer are 25℃~50℃.
7. The preparation method according to claim 6, characterized in that: The preparation method of the alginic acid dialdehyde includes, Sodium alginate was dissolved in a mixture of anhydrous ethanol and distilled water. Sodium periodate was added and the mixture was reacted in the dark at 40°C for 6 hours. Ethylene glycol was then added and the mixture was stirred for 30 minutes to terminate the reaction. Dialyze the reaction solution for 24 hours, changing the distilled water several times during this period, until no iodate remains; Finally, the dialysis solution was freeze-dried to obtain alginate dialdehyde.
8. The preparation method according to claim 1, characterized in that: After preparing the chitosan solution, tea polyphenols, and glycerol, they are assembled onto the obtained intermediate active layer. The chitosan concentration is 0.5%~3.0%, the glycerol concentration is 0.1%~0.5%, the tea polyphenol concentration is 0.01%~0.50%, and the film-forming conditions are 25℃~50℃.
9. The chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenol trilayer membrane prepared by any one of the preparation methods according to claims 1 to 8, characterized in that: The three-layer membrane has a tensile strength of 15 MPa to 25 MPa, an elongation at break of 18% to 22%, and a water vapor barrier value of 2 × 10⁻⁶ MPa. -12 ~4×10 -12 g·m -1 ·s -1 ·Pa -1 The oxygen barrier property is 3 × 10 -7 -6 ×10 -7 g·m -1 ·s -1 It has a DPPH free radical scavenging rate of 18-98% and has antibacterial effects against Staphylococcus aureus and Escherichia coli.
10. The application of the chitosan / alginic acid dialdehyde-cinnamaldehyde / chitosan-tea polyphenols three-layer film according to claim 9 in the preparation of food-grade packaging materials.
Citation Information
Patent Citations
Sodium alginate-chitosan double-layer edible membrane as well as preparation method and application thereof
CN107840981A
Preparation method of food-grade antibacterial plastic
CN114957811A
Alginate dialdehyde / chitosan anti-fog antibacterial film and preparation method thereof
CN111138696A
Natural polymer type antibacterial chitosan-NaCl usingchitosan, alginic acid and process for preparing thesame
KR1020010103538A